A multi-antigen vaccinia vaccine broadly protected mice against SARS-CoV-2 and influenza A virus while also targeting SARS-CoV-1 and MERS-CoV - Nan Gao; Tianhan Yang; Lanlan Dong; Wanda Tang; Kangli Cao; Kangli Cao; Longfei Ding; Cuisong Zhu; Shimeng Bai; Ai Xia; Youwei Zhu; Chen Zhao; et al. (Frontiers in Immunology)
IntroductionCoronaviruses and influenza viruses are significant respiratory pathogens that cause severe disease burdens and economic losses for society. Due to their diversity and evolution, vaccines typically require periodic updating to remain effective. An additional challenge is imposed by the possible coinfection of SARS-CoV-2 and influenza, which could increase disease severity.MethodsWe developed a vaccinia vaccine, named rTTV-RBD-HA2, broadly targeting coronaviruses and influenza viruses. This vaccine expresses three fusion proteins, each comprising the receptor-binding domain (RBD) from one of the three highly pathogenic coronaviruses (SARS-CoV-2, SARS-CoV, and MERS-CoV) and the conserved HA stalk region from two influenza viruses (pdmH1N1 and nH7N9) belonging to groups 1 and 2, respectively.ResultsThe multi-targeting nature of this vaccine was validated by its success in inducing antibody responses to the three RBDs and both group 1 and 2 HAs in mice. Importantly, it also generated robust T cell responses to all the immunogens, which could be mobilized to the lung through intranasal vaccination. Consistent with this broad immunogenicity profile, when administered via intramuscular priming and two intranasal boosts, rTTV-RBD-HA2 effectively protected vaccinated mice against challenges of the wild-type SARS-CoV-2 virus, the Omicron XBB variant, and the influenza A H1N1 and H3N2 viruses.DiscussionOur results collectively support the candidacy of recombinant rTTV-RBD-HA2 as a novel respiratory virus vaccine that provides cross-protection against coronaviruses and influenza viruses, surpassing the breadth of previous vaccines. Additionally, they underscore the importance of establishing a strong mucosal T cell response in the development of a universal respiratory virus vaccine.